Hollow gold nanostructures prepared by galvanic replacement reaction: synthesis and optical properties - Dung, Ngo T.; Lu, Le T.; Dung, Thieu T.; Duong, Vu T. T.; Hung, Nguyen V.; Vinh, Pham V.; Vuong, Nguyen T.; Fernig, David G. (Vietnam Journal of Science and Technology, 2015)
This work describes a facile synthesis of hollow Au nanostructures involved in the galvanic replacement reaction utilising Ag nanoparticles as the templates. The effect of reaction conditions, including PVP concentration and reaction time on the morphology of Ag templates was investigated. Using Ag nanocubic-shape templates, 50 nm hollow Au nanostructures were prepared. The result indicated that the wavelength of SPR peak of the hollow Au nanostructures was strongly affected by Au precursor content and could be tuned between 460 and 860 nm when altering the volume of the Au precursor solution from 0.5 to 3 ml. The ability of conversion of photo energy into heat of the hollow Au nanostructures was also exploited. The optical heating data of Au solution (165 µg/ml) with an 808 nm laser at a power of 1.8 W showed that the sample temperature reached to 55 oC after just 5 min irradiation. The successfulness in fabrication hollow Au nanostructures having SPR peak in NIR region, relative small size and high capacity of conversion of photo energy into heat make them become a novel and promising material for photo thermal and photo imaging applications.